Influences of polymorphic variants of DRD2 and SLC6A3 genes, and their combinations on smoking in Polish population - Niedoszytko Marek; Jassem Ewa; Buczkowski Krzysztof; Sieminska Alicja; Tkacz Ewa (BMC, 2009)
Abstract Background Polymorphisms in dopaminergic genes may influence cigarette smoking by their potential impact on dopamine reward pathway function. A1 allele of DRD2 gene is associated with a reduced dopamine D2 receptor density, and it has been hypothesised that A1 carriers are more vulnerable to smoking. In turn, the 9-repeat allele of dopamine transporter gene (SLC6A3) has been associated with a substantial reduction in dopamine transporter, what might result in the higher level of dopamine in the synaptic cleft, and thereby protective role of this allele from smoking. In the present study we investigated whether polymorphic variants of DRD2 and SLC6A3 genes and their combinations are associated with the smoking habit in the Polish population. Methods Genotyping for TaqIA polymorphism of DRD2 and SLC6A3 VNTR polymorphism was performed in 150 ever-smokers and 158 never-smokers. The association between the smoking status and smoking phenotypes (related to the number of cigarettes smoked daily and age of starting regular smoking), and genotype/genotype combinations was expressed by ORs together with 95% CI. Alpha level of 0.05, with Bonferroni correction whenever appropriate, was used for statistical significance. Results At the used alpha levels no association between DRD2 and SLC6A3 genotypes and smoking status was found. However, A1 allele carriers reported longer abstinence periods on quitting attempts than non-carriers (p = 0.049). The ORs for heavier smoking were 0.38 (0.17-0.88), p = 0.023, and 0.39 (0.17-0.88), p = 0.021 in carriers compared to non-carriers of A1 or *9 allele, respectively, and the OR for this smoking phenotype was 8.68 (2.47-30.46), p = 0.0005 for the A1-/9- genotype combination, relatively to the A1+/9+. Carriers of *9 allele of SLC6A3 had over twice a lower risk to start smoking before the age of 20 years compared to non-carriers (sex-adjusted OR = 0.44; 95% CI: 0.22-0.89; p = 0.0017), and subjects with A1-/9- genotype combination had a higher risk for staring regular smoking before the age of 20 years in comparison to subjects with A1+/9+ genotype combination (sex-adjusted OR = 3.79; 95% CI:1.03-13.90; p = 0.003). Conclusion Polymorphic variants of DRD2 and SLC6A3 genes may influence some aspects of the smoking behavior, including age of starting regular smoking, the level of cigarette consumption, and periods of abstinence. Further large sample studies are needed to verify this hypothesis.